REVIEW PAPER ON FOOTSTEP POWER GENERATION SYSTEM USING MICROCONTROLLER - Miss. Kulkarni M. S; Mr. Harwalkar. S. M; Mr. Gaikwad S. R; Miss. Dhallu S. A; Miss. Tonage R. A. (International Engineering Journal For Research & Development, 2021)
Day by day, the population of the country increased and the requirement of the power is also increased. At the same time the wastage of energy also increased in many ways. So reforming this energy back to usable form is the major solution. As technology is developed and the use of gadgets, electronic devices also increased. Power generation using conservative methods becoming deficient. There is a necessity arises for a different power generation method. At the same time the energy is wasted due to human locomotion and many ways. To overcome this problem, the energy wastage can be converted to usable form using the piezoelectric sensor. This sensor converts the pressure on it to a voltage. So by using this energy saving method which is the footstep power generation system we are generating power.